Ocorrência de arsênio, cádmio e chumbo em tecidos de aves, suínos, bovinos de corte e equinos no Brasil - Juarez Fabiano de Alkmim Filho (2011)
Among the major inorganic contaminants present in animal products, cadmium, arsenic and lead stand out. The aim of this study was to investigate the presence of residues of cadmium, arsenic and lead in samples of liver, kidney and muscle of cattle, poultry, swine and horses. It was used 3046 samples from 20 Brazilian States. The samples were analyzed at the National Agricultural Laboratory (LANAGRO-MG) using the technique of atomic absorption spectrometry. In bovine samples the average values of arsenic found in liver and kidney were 27.42 and 30.55g/kg respectively. In comparison to lead the averages found in liver (231.93g/kg) and kidneys (226.96g/kg) were below the MRL values (500g/kg). Mean levels of cadmium were 207.53 and 197g/kg for liver and kidney, respectively. In samples of poultry the mean values of arsenic found in the liver, kidney and muscle were 333.6, 137.7 and 32.6g/kg, respectively. For cadmium and lead the averages were 176.6, 286.3, 191.8 and 220.8g/kg, respectively. In porcine samples the average value of arsenic found in the liver was 58.5g/kg. For cadmium and lead the averages found were 172.1, 217.9, 281.4 and 207.2g/kg respectively. In samples from horses the maximum level of arsenic was 50g/kg. In summary, during all seven years, only 17 out of 3046 tested samples would violate the legislation. The average contamination and percentage of samples contaminated with cadmium have shown an upward trend in the recent years especially in cattle and swine, although few samples exceeded the MRL. The occurrence of arsenic contamination has decreased significantly in recent years possibly due to greater government control over the main potential sources of arsenic in animal feed. The frequency of lead waste was low in all species, especially poultry and porcine and its occasional occurrence is probably linked to the specific problems of environmental pollution